ANALISIS KEBERHASILAN SEKOLAH LAPANGAN PENGELOLAAN TANAMAN TERPADU (SL-PTT) PADA USAHATANI JAGUNG DI DESA MEKAR SARI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Aprollita; Lawensha, Miko; Siata, Ratnawati (Universitas Jambi, 2019)
This study was conducted to determine the success of Integrated Crop Management Field School (FFS-ICM) and analyze the results of the productivity of corn in corn farm in the village of Mekar Sari subdistrict Kumpeh Muaro Jambi. Sampling method using cluster sampling method with a sample of 72 respondents. Statisti analyzed using inferential. Inferential statistical techniques were used in this study is a paired t test (Paired sample t test). Discussion of the results of analysis of Integrated Crop Management Field School (FFS-ICM) to give effect to the knowledge, attitude and application of agricultural technology, it can be seen from the differences in knowledge, attitudes, and before the application of agricultural technology between the SL-PTT after the implementation of SL- PTT. The results of different tests in pairs on each component of agricultural technology showed tcount> ttable, meaning that there are differences in both the knowledge, attitudes, as well as the application of the prior Field School of Integrated Crop Management (SL-PTT) and after the Field School of Integrated Crop Management (SL-PTT). Similarly, the results of the productivity of maize